Menjaga Kesehatan Mental Ditempat Kerja - Jesika Pasaribu; Yunita Astriani Hardayati (AMMA : Jurnal Pengabdian Masyarakat, 2025)
A worker experiences job stress when there is an imbalance between work and the ability to cope with stress. Work-related stress can occur due to organizational, individual and other factors. An employee should ideally have low job stress and a light workload, but in many situations job stress can result from a high workload. If not addressed it can reduce productivity and work performance and affect physical and mental health. The purpose of this community service is to increase employee knowledge about work stress and overcome stress by means of stress management. The method of activity is direct counseling using power points, discussion and roleplay. The material provided is about work stress and stress management. The participants were employees at PT.X Bekasi. This community service activity in the form of education can increase workers' knowledge in recognizing work stress and the ability to overcome problems at work. It is expected that along with improving the ability to cope with stress, it can improve performance and mental health in the workplace.